Pengaruh Penggunaan Media Sosial Instagram @fdxbeauty Terhadap Keputusan Berkunjung Pada Event Jakarta X Beauty Tahun 2022 - Putri, Zahra Ananda (Brand Communication, 2023)
Humans are social beings whose activities certainly require communication. In today's development, social media is a term that describes that there are various kinds of technologies that are used to bind people in a collaboration, where with the existence of technology it is possible to exchange information, and interact with each other through messages conveyed via the internet. The beauty industry is growing in Indonesia due to the increasing number of social media users so that beauty influencers are growing which of course has a big impact on the world of beauty. One of the companies in the beauty sector, namely Female Daily, is a company that is developing in the digital era, Female Daily makes good use of social media and can connect people who have an interest in the world of beauty so that the Instagram account @fdxbeauty is formed, which is an official account made by Female Daily with the aim to promote and present the X Beauty by Female Daily event. This study aims to see the influence of the use of social media Instagram @fdxbeauty on the decision to visit the Jakarta X Beauty 2022 event and how big the influence is. This study uses quantitative methods and data collection techniques used are questionnaires. The sampling technique used was purposive sampling with 100 respondents who were Instagram followers @fdxbeauty and visitors to the Jakarta X Beauty 2022 event. The results showed that there was an influence between the use of social media Instagram @fdxbeauty and the decision to visit the event. Jakarta X Beauty 2022 with 32.8%. The researcher's suggestion is that further research can be carried out using qualitative methods to dig deeper information from resource persons who have competence related to the use of social media Instagram @fdxbeauty.